IFPRI research and training activities in Eastern Africa - Bolwig, Simon (International Food Policy Research Institute, 2000)
In 1998 IFPRI and its collaborators in Africa established two regional research networks, one for East Africa and one for West Africa. Unlike most research-based entities, these networks include not only researchers, but policymakers and leaders from civil society. Through research, publications, training, and dialog between but decisionmakers and researchers, the networks aim to generate information that policymakers can use to encourage sustainable growth and poverty-alleviation goals and to build the capacity of African countries to formulate appropriate policies and strategies. Through research, publications, training, and dialog between ministries, research or academic institutions, and civil society organizations. The overall goal of the 2020 Vision networks is to reduce poverty, improve food security and child nutrition, improve gender equity, increase agricultural productivity, and promote sustainable use of natural resources. The networks aim to fulfill these objectives specifically by integrating themselves in national and regional-level policymaking processes, working closely together with local researchers, policymakers, and civil society organizations. The East African network comprises Ethiopia, Kenya, Malawi, Mozambique, Tanzania, and Uganda. The network has formed country teams headed by leading researchers and policymakers from each country. The teams are drawn from government ministries, research or academic institutions, and civil society organizations.